2004
DOI: 10.1017/s1047951104002100
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function and ventricular perfusion defects in adults with congenitally corrected transposition: correlation of echocardiography and nuclear medicine

Abstract: We undertook our study in order to evaluate right ventricular function and perfusion by conventional and contrast echocardiography in adults with congenitally corrected transposition who had not undergone cardiac surgery, comparing the echocardiographic findings with those obtained using equilibrium radionuclide ventriculography and gated single-photon emission computed tomography with Technetiumc-99 m sestamibi. We discovered severe tricuspid regurgitation in 8 patients (61%). Right ventricular ejection fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In patients with congenitally corrected transposition or transposition after Mustard or Senning operation, ischaemic perfusion defects, together with chronic volume overload from tricuspid regurgitation and long-standing pressure overload, are the determining factors of right ventricular dysfunction. [15][16][17][18] Moreover, cardiopulmonary bypass with inflammatory mediators and hypothermic circulation arrest (often multiple exposure), tricuspid valve surgery, significant arrhythmia, and pacemaker therapy are well-known risk factors for systemic right ventricular dysfunction. 2,19 Interestingly, Doughan et al 20 has also reported that b-blockers, carvedilol or metoprolol, in patients with transposition and systemic right ventricular dysfunction resulted in improvement of New York Heart Association functional class and such improvement was more important in patients with pacemakers who could receive higher maintenance doses of b-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with congenitally corrected transposition or transposition after Mustard or Senning operation, ischaemic perfusion defects, together with chronic volume overload from tricuspid regurgitation and long-standing pressure overload, are the determining factors of right ventricular dysfunction. [15][16][17][18] Moreover, cardiopulmonary bypass with inflammatory mediators and hypothermic circulation arrest (often multiple exposure), tricuspid valve surgery, significant arrhythmia, and pacemaker therapy are well-known risk factors for systemic right ventricular dysfunction. 2,19 Interestingly, Doughan et al 20 has also reported that b-blockers, carvedilol or metoprolol, in patients with transposition and systemic right ventricular dysfunction resulted in improvement of New York Heart Association functional class and such improvement was more important in patients with pacemakers who could receive higher maintenance doses of b-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, poor tolerance of the systemic AV valve to systemic pressure after VSD closure is possible because afterload is increased, and postoperative complete AV block may compound the adverse hemodynamics. The observation of progressive systemic AV valve regurgitation after operative intervention has prompted some authors to recommend systemic AV valve replacement at the time of intracardiac repair if the systemic AV valve regurgitation is moderate or more at the time of surgery [ 26 ].…”
Section: Outcomes Of Systemic Atrioventricular Valve Surgerymentioning
confidence: 99%
“…Le document complet et les références figurent également aux adresses www.ccs.ca et www.cachnet.org. course of coronary arteries are present in one-third of patients, and an intramural coronary artery course is present in 3% to 4% (1,2).…”
Section: La Conférence Consensuelle 2009 De La Société Canadienne De mentioning
confidence: 99%